Programmable Base Editing of the Sheep Genome Revealed No Genome-Wide Off-Target Mutations - Zhou, Shiwei; Cai, Bei; He, Chong; Wang, Ying; Ding, Qiang; Liu, Jiao; Liu, Yao; Ding, Yige; Zhao, Xiaoe; Li, Guanwei; Li, Chao; Yu, Honghao; et al. (Frontiers in Genetics, 2019)
Since its emergence, CRISPR/Cas9-mediated base editors (BEs) with cytosine deaminase activity have been used to precisely and efficiently introduce single-base mutations in genomes, including those of human cells, mice, and crop species. Most production traits in livestock are induced by point mutations, and genome editing using BEs without homology-directed repair of double-strand breaks can directly alter single nucleotides. The p.96R>C variant of Suppressor cytokine signaling 2 (SOCS2) has profound effects on body weight, body size, and milk production in sheep. In the present study, we successfully obtained lambs with defined point mutations resulting in a p.96R>C substitution in SOCS2 by the co-injection of Base Editor 3 (BE3) mRNA and a single guide RNA (sgRNA) into sheep zygotes. The observed efficiency of the single nucleotide exchange in newborn animals was as high as 25%. Observations of body size and body weight in the edited group showed that gene modification contributes to enhanced growth traits in sheep. Moreover, targeted deep sequencing and unbiased family trio-based whole genome sequencing revealed undetectable off-target mutations in the edited animals. This study demonstrates the potential for the application of BE-mediated point mutations in large animals for the improvement of production traits in livestock species.